SIFAT PEMESINAN 13 JENIS KAYU DARI ACEH - Bakir Ginoga (Jurnal Penelitian Hasil Hutan, 1996)
The qualities of machining properties of 13 wood species from natural forest in Aceh were investigated in air dried condition. Wood species are bayur (Pterospermum elongatum Korth.),keranji (Dialium indum L. var. Indum), sebusuk (Amoora rubiginosa (Hiern.) Pance), runding (Parkia javanica (Lamk.) Merr.), kilulun (Artocarpus gomezianus Wall. ex Tree), anglau (Garcinia nervosa Miq.), alifambang (Endospermum diadenum Miq. Airy Shaw), bentol (Kokoona reflexa), batu-batu (Xanthophyllum excelsum Miq.), bayut (Mezzettia parviflora Becc.), nurai (Cananga odorata Hk. f Th.), alatat (Sonneratia caseoflaris Engl.) and pinang baek (Gonystylus macrophyllus Airy Shaw.).The results revealed that the qualities of machining properties of wood tested mostly belong to good (class ll) until very good quality (class I).Key words : machining property, wood species, Aceh, air dried